“Determinación de las propiedades Físicas y Mecánicas de la fibra de algodón de las variedades (Áspero blaco), ( Línea-1), (Línea-40) y (upland bja-594) cultivadas en la región de san martín - Flores Flores, Mercy Mariela (2003)
This study sought to determine the best variety and zone of cotton plantation in 6 places of Region San Martin with the object to recommend its cultivation with Agroindustrial purposes. Above all firstly were evaluated its physical -mechanic properties of cotton fiber (Gossypium sp ) taking samples of varieties Aspero blanco, Une "01", Une "40", and Upland BJA - 594 from following places: Saposoa, San Martin, Juanjui, Picota, Bellavista and Dorado. The physical -mechanic analysis gave as a result that fiber of variety Upland- 594 has most length (29.07 mm - juanjui), most resistance (29.13 g./tex - San Martin) , most fine (4.13 μ - Saposoa). Wlth regard to the elasticity this variety (Upland BJA - 594) had minor about, being reported the raisest ir. province Juanjui with 6.13%. The fibre that presented the best elasticity found in variety Une "01 n from Bellavista (7.77%) which don't qualify as the best variety for having a low result in comparison with the other fibre properties of variety Upland BJA - 594 and for having a low acceptance to realize sensorial analysis for color and texture attributes. The highest Line"01 n, found in following places: Length (27 .07 mm) in Saposoa, Resistance (27 .83 g./ tex) in Bellavista, and the finest fibre found in San Martin (7 .17 μ). To realizing the analysis of variance was determined donit exist significant difference to 5% in probability _ between origin places about cotton fiber, but existing significant difference between study - four varieties that wo.s made a comparison of average through the Tukey's test, whose result gave to the fibre of variety Upland BJA - 594 which has the best physical -mechanic properties, moreover don't exist significant difference to 5 % in probability between varieties Áspero blanco, Une "01 n. Une "40n. On the other hand, the sensorial analysis on cotton fiber determined that most softness and best color (most white) holds variety Upland BJA - 594 from Juanjui, Bellavista, Saposoa, Picota and San Martin. The choice for the best variety of cotton was carried out taking into account results of fibres analysis and its sensorial evaluation about acceptability, giving as a result to variety Upland BJA - 594 that has the best physical-Mechanic properties, also for being the softest and for having the best color. The place were has seen the best results is the province Juanjui, respectively.